Evaluation of exposure to cyanogenic glycosides and potential hydrogen cyanide release in commercially available foods among the Korean population - Hana, Park; Chung, Hyun; Choi, Shinai; Bahn, Yong-Sun; SON, Jung hyun (Elsevier BV, 2024)
The release of hydrogen cyanide (HCN) after food ingestion can pose a serious health risk to consumers. This study aimed to simultaneously quantify four cyanogenic glycosides (lotaustralin, prunasin, taxiphyllin, and dhurrin) using liquid chromatography？tandem mass spectrometry. The analysis scope extended beyond agricultural products to various consumer foods to estimate dietary exposure to cyanogenic glycosides and assess its risk levels. The major exposure sources are cassava chips (lotaustralin), apples (seeds) (prunasin and dhurrin), and Prunus mume axis (taxiphyllin). In addition to quantifying specific cyanogenic glycosides, this study proposed the development of a preliminary risk assessment framework based on the dietary exposure assessment and the calculation of theoretical levels of HCN derived from cyanogenic glycoside concentrations. In the absence of established guidelines for the permissible intake of foods containing cyanogenic glycosides, this study provides initial guidance for assessing the risks associated with a range of commonly consumed foods.